(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Permeability or Hydraulic conductivity of soil is basic property of soil that needs to be taken into consideration when planning a Civil engineering project. In most of the Civil engineering projects a low permeable soil is desired over high permeable soils. In areas like deserts, the construction industry is facing a number of challenges due to non availability of permeable soils. Kaolin is a naturally occurring fine grained clayey soil that can be obtained in abundance at very low costs. In this study samples with different proportions (0%, 5%, 10%, 15%, and 20%) of sand-Kaolin were tested for the variations in permeability (vertical permeability) of sand. The tests were performed through constant head permeability methods and variable head permeability methods. The main aim of our study was to test the capability of Kaolin to decrease the permeability of sand. The results indicated a steep decrease in permeability of sand till 10% Kaolin clay content, afterwards a gradual decrease was observed. The coefficient of permeability of sand was decreased by 99.3% by increasing Kaolin content to 10% from 0%. This low permeable sand thus obtained could be potentially used as a filler material, vertical backfills to cut off the seepage through sandy soils, low permeable embankments, etc.